Preservation of Newspaper Clippings From CSIS (Centre for Strategic and International Studies) Collection at the National Library of the Republic of Indonesia - Frisca Vania Audy; Ute Lies Siti Khadijah; Yunus Winoto (Jurnal Pustaka Ilmiah, 2025)
Newspaper clipping preservation prevents collections from damage so that they can last a long time and still be used by future generations. Newspaper clippings from the CSIS (Centre for Strategic and International Studies) collection have the advantage of containing more authentic and primary information, and they have been arranged based on specific subjects, making it easier for users. This study aimed to determine the preservation of newspaper clippings from the CSIS collection at the National Library using the preservation pyramid. The method used was qualitative with a case study approach. The study results showed that the National Library had carried out preservation activities that included preventive preservation, passive conservation, active conservation, and restoration per the preservation pyramid. Preservation efforts carried out were in the form of compiling preservation policies, preventing damage to collections due to environmental and human factors, training for librarians, managing the storage environment in the form of air conditioning and curtains, binding, and fumigation in 2 collection rooms owned by the National Library. However, restoration has not been implemented because the condition of the collection is still quite good, although there is a risk of damage to clippings that have not been processed, so a policy is needed to continue the preservation of newspaper clippings from the CSIS collection.